The Role of Job Satisfaction as a Mediation on Manager Performance: Influenced by Competence and Intelligence - Ajar Siswandono; Djoko Soelistya; Tri Cicik Wijayanti; Suyoto Suyoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Every company certainly wants to achieve maximum performance. The level of performance in the company is a very important benchmark or persona. And the phenomenon that occurs in frozen food companies is a decrease in Manager level performance in carrying out their functions and duties due to changes in behavior, work environment, competencies of Managers in accordance with educational backgrounds and years of service that support their competencies.”"This study aims to analyze the influence of Competence and Intelligence on Manager Performance whether there is a need for Job Satisfaction as a mediation, and this study uses quantitative methods with SmartPLS 3.0 analysis, the population of managers is 60 respondents, and the results of the study show that (1) Competence does not have influence on manager performance; (2) Intelligence has no influence on performance; (3) Competence has no effect on Job Satisfaction; (4) Intelligence has an influence on Job Satisfaction; (5) Job Satisfaction has an influence on performance; (6) Competence can have a direct effect on the performance of managers even without going through job satisfaction, the competencies that have been given by the company are maintained and their human resource development programs are improved, while (7) Intelligence can have a direct effect on the performance of managers but must go through job satisfaction, it is necessary to have trust in managers so that they feel satisfied that their work is appreciated.